THE EVALUATION OF LANGUAGE TEACHING PROGRAM APPLIED IN THE SCHOOL OF FOREIGN LANGUAGES - Gülten Genç; Emine Kuluşaklı (Informascope, 2019)
English language teaching is one of the most crucial issues in the field of education in the world as well as in Turkey. There has been a growing need for adequate English language education programs at schools in Turkey. Preparatory classes of the School of Foreign Languages which offers students a full one year of English education try to fulfill this need regarding the students' needs and wishes into consideration in order to teach English successfully. For that reason, this study focused on the evaluation of the effectiveness of language teaching program applied in the preparatory classes by the school of Foreign Languages of a state university in Turkey through the perspectives of the students studying English for a year. 270 students attending the preparatory school participated in the study. The data were gathered through a self-reported student questionnaire and were analyzed descriptively through SPSS 20. The results of the study demonstrated that the language teaching program in the preparatory classes of the School served for its purpose not fully but partially. The findings of the study indicated some significant implications in relation to the strengths and weaknesses of the program. It would give some clues to the administration to understand the effectiveness of the Program.